Relationship between functional mobility and falls in women with knee osteoarthritis - Cipolli, Jamilly Radiuc [UNESP]; Navega, Marcelo Tavella [UNESP]; Spinoso, Deborah Hebling [UNESP] (Elsevier, 2024)
Background Osteoarthritis is the most prevalent rheumatic illness in the population, characterized by progressive loss of joint cartilage and subchondral bone sclerosis that results in functional limitation. Among the affected joints, the knee is the most injured. Pain, muscle weakness, reduced balance and reduced movement range are the main symptoms of patients with knee osteoarthritis (KOA) and they may contribute to a decrease in functional mobility and a greater possibility of falls in this population. Objectives The study aims to compare the functional mobility in women with and without KOA, relating it to the number of falls. Methods Were chosen 71 people, who were divided into two groups, the studied one with Knee Osteoarthritis (GOAJ: n = 39; 66,8 ± 7,7 years) and the control group (GC: n = 32; 64,9± 7,1 years). The research project was approved by the local ethics committee (1.503.496/2015) and all the participants had signed the free informed consent term and agreed to join the study. Firstly, anamnesis was done to obtain personal data and the number of falls in the last 12 months. To assess functionality, the Short Physical Performance Battery (SPPB) was applied, consisting of three items: assessment of balance, gait speed and, indirectly, lower limb strength, through the sit-to-stand test. For statistical analysis, the T-test for Independent Samples was used, considering a significance level of p < 0,05. Results Women with KOA had a 48% lower gait speed (p < 0,001) and a 30% higher time to sit down and stand up from a chair for five consecutive times (p < 0,001), compared to the control group. No significant difference was found in the balance tests of both groups. The group with KOA (GOAJ) showed an average of 2,7 falls in the last twelve months, while the control group (GC) showed an average of 1,4 falls. There was a negative correlation between gait speed and sitting down/standing up time with the number of falls. Conclusion Women with KOA have decreased functional mobility, and this may contribute to a higher occurrence of falls in this population. Implications The study shows that women with KOA have decreased functional mobility, which can negatively affect the performance of activities of daily living and the quality of life of this population.